Neuromarketing and purchasing decision in consumers of the Departamento de Huánuco (Department of Huanuco), Peru - Chicoma Ruiz, Giuliana del Pilar (2021)
Objective. To establish the relationship between neuromarketing and the purchase decision of Coca-Cola consumers in the city of Huánuco, 2019. Methods. The research had a quantitative approach of the basic type, design and correlational descriptive research level; data were collected through a survey to know the behavior of the study variables in the clients. Results. As demonstrated in this research, it is attested that neuromarketing is significantly related to the purchase decision of Coca-Cola products in the city of Huánuco, 2019. (Sig.=0.001). Conclusions. Through the executed research it is attested that neuromarketing is positively related to the purchase decision and this is reflected in the results obtained during the data processing.